SYSTEMATIC LITERATURE REVIEW OF SULFUR DIOXIDE SOURCES, IMPACTS, AND CONTROL STRATEGIES - rahmawaty rahmawaty; Andriadi; Sayyida Nafisa; Elma Asvira Vardhani; Suranto (Jurnal Belantara, 2026)
Sulfur dioxide (SO₂) remains an important ambient air pollutant in Indonesia because it is emitted by fossil-fuel combustion, industrial processes, vehicular activities, and open burning at waste-disposal and commercial areas. This systematic literature review synthesizes empirical evidence on SO₂ emission sources, ambient concentrations, health and ecological impacts, monitoring approaches, and control strategies in Indonesia. Literature published between 2018 and 2025 was identified from Scopus, ScienceDirect, PubMed/MEDLINE, Google Scholar, and WHO-related databases, and the review process was reported in accordance with PRISMA 2020. After duplicate removal, title and abstract screening, full-text eligibility assessment, and methodological appraisal, 55 studies were included in the synthesis. The evidence shows that elevated SO₂ concentrations are repeatedly reported in traditional markets, landfills, industrial zones, transport corridors, and public facilities, although the spatial coverage and monitoring duration remain uneven. Health-related studies indicate respiratory irritation, non-carcinogenic exposure risks among high-exposure workers, and potential exacerbation of chronic respiratory disease, while ecological impacts remain comparatively under-investigated. Bibliometric mapping using VOSviewer identified air pollution, sulfur dioxide, ambient air, air quality, public health, and health impact as the dominant thematic clusters. This review contributes by integrating source-exposure-impact-control evidence and by identifying the main methodological and policy gaps for SO₂ management in Indonesia.